The shifting drivers of global liquidity - Stefan Avdjiev; Leonardo Gambacorta; Linda S. Goldberg; Stefano Schiaffi (Federal Reserve Bank of New York, 2017)
The post-crisis period has seen a considerable shift in the composition and drivers of international bank lending and international bond issuance, the two main components of global liquidity. The sensitivity of both types of flows to U.S. monetary policy rose substantially in the immediate aftermath of the global financial crisis, peaked around the time of the 2013 Federal Reserve "taper tantrum," and then partially reverted toward pre-crisis levels. Conversely, the responsiveness of international bank lending to global risk conditions declined considerably after the crisis and became similar to that of international debt securities. The increased sensitivity of international bank flows to U.S. monetary policy has been driven mainly by post-crisis changes in the behavior of national banking systems, especially those that ex ante had banks that were less well capitalized. By contrast, the post-crisis fall in the sensitivity of international bank lending to global risk was mainly owing to a compositional effect, driven by increases in the lending market shares of national banking systems that were better capitalized. The post-2013 reversal in the sensitivities to U.S. monetary policy partially reflects the expected divergence in the monetary policies of the United States and other advanced economies, highlighting the sensitivity of capital flows to the degree of commonality of cycles and the stance of policy. Moreover, global liquidity fluctuations have largely been driven by policy initiatives in creditor countries. Policies and prudential instruments that reinforced lending banks' capitalization and stable funding levels reduced the volatility of international lending flows.
Keywords: F34; G10; G21; 330; global liquidity; international bank lending; international bond flows; capital flows; Finanzkrise; Internationale Liquidität; Internationale Bank; Kreditgeschäft; Anleihe; Kapitalmobilität; USA; Welt